Pengaruh Social Media dan Brand Image Terhadap Purchase Decision Melalui Buying Interest - Sutiyati Sutiyati*; Henny Welsa; Ambar Lukitaningsih (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2020)
ABSTRACTThe purpose of this research is to determine the most influential and important variables that cause the low totally of the peoples has been visited at Parangtritis beach Yogyakarta in accordance with the problems that have been formulated. A sample size of 97 that can represent the population is determined using the Krejcie-Morgan method. The method of analysis in this study is to use a variance-based analysis of Structural Equation Modeling (SEM), namely Partial Least Square (PLS). The sampling technique in this study is accidental sampling using a questionnaire instrument. Social media variables have a positive and significant effect on purchase decision by showing p values of 0.000; brand image variable has a positive and significant effect on purchase decision with p values of 0.018; social media variables has a positive and significant effect on buying interest and p values of 0.008; brand image variable has a positive but not significant effect on work stress with an original sample value of 0.213 and a p value of 0.129; buying interest variables have a positive and significant effect on purchase decision as evidenced by the original sample value of 0.014 and p values of 0.764; buying interest as intervening influences has effect on relationship between social media variables and purchase decision with zscore (2.67)> ztable (1.96); buying interest as an intervening has not effect on relationship between brand image and purchase decision  with  zscore (1.08)< ztable (1.96).Keywords: Social media, Brand image, buying interest, purchase decision